PENTINGNYA REORIENTASI PEMBELAJARAN DALAM PENERAPAN KURIKULUM BERBASIS KOMPETENSI - Wagiran Wagiran (Jurnal Cakrawala Pendidikan, 2005)
AbstractGlobalization need Human Resources (HR) having competitivenessopenly with other state, adaptif and anticipative to various new condition and change, can learn how to learning, multi-skilling, re-trained easy, and also have wide of ability bases, strength, and basis for expand in the future. Job market a period of coming will mark by uncertainty, faster, often change, and claim high flexibility. Someone do not only claimed to have ability in working, but also have accomodation-power to change, ability and independence to expand, to solving problem and is skilled of socialCompetence Based Curriculum (CBT) represent education innovationin the effort preparing global HR era. In its learning, CBT want the existence of learning reorientation of model of teaching to model of learning with educative participant centre on (student centered learning).This model place student as learning subyek which must be active develop its ability. Learning have the character of actively, partisipative and kolaboratif and also by totally all aspect efficiency of specific life and also generik. Teacher functioning instructor as learning manager and fasilitator. According to principle mastery learning and developmentof talent, every educative participant have to give by opportunity to reach target down alley and speed learn him. Assessment done by holistic, concerning learning process and result.Learning of constructivistic, Contextual Teaching and Learning, learn active and assessment holistic represent learning model giving bigger opportunity in improving the quality of education utilize to prepare global HR era.Key words: Reorientation of Learning, Competence Based Curriculum,human resources